The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/trf.16599
|View full text |Cite
|
Sign up to set email alerts
|

Causes of an elevated international normalized ratio in the intensive care unit and the implications for plasma transfusion

Abstract: Background: The presence of an elevated international normalized ratio (INR) is common in patients in the intensive care unit (ICU), but the cause rarely determined. These patients are at risk to receive prophylactic plasma prior to invasive procedures.Study design and methods: Samples from patients with an INR of 1.5 or greater were frozen and subsequently thawed and assayed for procoagulant and anticoagulant clotting factors and anti-Xa to determine the likely cause of the INR. Samples showing a low FVII, FX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This scoping review is the first to explore the mechanisms and consequences of vitamin K deficiency in this population. Six studies analyzing ICU patients' vitamin K status indicate many patients may have (sub)clinical deficiency upon admission and during their stay [ 14 16 , 83 , 114 , 115 ]. Deficiency may appear subclinical with normal PT but high PIVKA levels, possibly masking extrahepatic vitamin K function due to hepatic carboxylation favoring [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review is the first to explore the mechanisms and consequences of vitamin K deficiency in this population. Six studies analyzing ICU patients' vitamin K status indicate many patients may have (sub)clinical deficiency upon admission and during their stay [ 14 16 , 83 , 114 , 115 ]. Deficiency may appear subclinical with normal PT but high PIVKA levels, possibly masking extrahepatic vitamin K function due to hepatic carboxylation favoring [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 In a recent study, we have observed that a large percentage of these patients (40%) have a clotting factor pattern more consistent with vitamin K deficiency. 5 Therefore, we believe that before a study of prophylactic plasma should be performed, the cause of the elevated INR should be identified in order to avoid the "one intervention (prophylactic plasma) fits all elevated INRs approach. "…”
Section: Elevated Inr In the Icu And Plasma Transfusionmentioning
confidence: 99%